A Study of Artificial Intelligence in Human Resource Management - Gaurav Kumar Das (International Journal of Advanced Science and Technology, 2020)
Contemporary organizations around the globe, strive for efficiency at a faster pace with the help of technology to face competition. Human Resource Management plays an essential role by pooling in the necessary human capital in the organization along with required skill, in order to execute the goals of the organization. Advancements in technology have paved for the organizations to complete its organizational tasks, operational and non operational at a faster pace, which would have otherwise been dependent completely on manual process. It is the need of the hour to assess the role of artificial intelligence in the area of human resource.PURPOSE: The objective of the study is to examine the role of artificial intelligence in recruiting of human Resource along with its challenges. The secondary objective of the study is to suggest measures for adopting AI in the traditional recruitment areas.METHOD: The study is descriptive in nature and has used secondary data to assess its objectives. The study depended on previous research publications, websites and HR blogs.CONCLUSION: The study has identified that the area of Artificial Intelligence is still at its inception in discharge of recruitment duties and even on its entered ventures it strives to achieve more advancements. The study from its referred literature has identified that in the stages of pre and post recruitment process, AI plays a predominant role.